2010
DOI: 10.1007/s11423-010-9148-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and effects of representational scripting on group performance

Abstract: This study investigated the effects of representational scripting on non-expert student learning while collaboratively carrying out complex learning-tasks. The premise underlying this research is that effective cognitive activities would be evoked when complex learning-tasks are structured into phase-related part-tasks and are supported by providing students with part-task-congruent external representations for each phase; representational scripting. It was hypothesized that this approach would lead to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This is consistent with previous findings (e.g., Noroozi et al., 2013; Stegmann et al., 2007) that the use of discussion script can stimulate meaningful interaction and encourage deep thinking for solving a problem collaboratively. The results of this study also reveal that these interactions lead to higher levels of collaborative learning performance, as suggested previously (Beers et al., 2005; Slof et al., 2010). Other types of higher order interactions such as questioning, consensus-building, and judgment were also indirectly affected by the learning conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous findings (e.g., Noroozi et al., 2013; Stegmann et al., 2007) that the use of discussion script can stimulate meaningful interaction and encourage deep thinking for solving a problem collaboratively. The results of this study also reveal that these interactions lead to higher levels of collaborative learning performance, as suggested previously (Beers et al., 2005; Slof et al., 2010). Other types of higher order interactions such as questioning, consensus-building, and judgment were also indirectly affected by the learning conditions.…”
Section: Discussionsupporting
confidence: 89%
“…There have been studies adapting scaffolding for CSCL tools while considering progressive problem-solving processes (Slof et al., 2010; Suthers & Hundhausen, 2003; Kobbe et al., 2007). Slof et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Externalizing the key cognitive aspects (e.g., searching for information and data, constructing domain knowledge, and hypothesizing and reasoning) in a holistic way is critical for successful inquiry learning. Second, the choice of representational tools should align with the characteristics and demands of the problem or task (Cox, ; Slof, Erkens, Kirschner, & Jaspers, ). The 3DTG used in this study has shown promising effects in externalizing and facilitating complex hypothesizing of causal relations and reasoning on the basis of relevant data and subject knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Slof, Erkens, Kirschner, & Jaspers (2010) successfully applied model order progression to a businesseconomics task. They distinguished three models (a conceptual, causal, and simulation model) that essentially resemble the current study's model order progression phases.…”
Section: Discussionmentioning
confidence: 99%